2020
DOI: 10.1093/humrep/deaa101
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of circadian desynchrony on the male reproductive system: an epidemiological and experimental study

Abstract: Abstract STUDY QUESTION Is circadian desynchrony a risk factor of male reproductive damage in semen parameters and/or reproductive hormones? SUMMARY ANSWER Circadian desynchrony correlates with decrease of sperm count, which was improved when circadian desynchrony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…They found that rotating shift work is related to lower sperm counts. They also found negative effects in sperm count non-work-related causes, like long time use of the mobile phone [ 117 ].…”
Section: Lifestylementioning
confidence: 99%
“…They found that rotating shift work is related to lower sperm counts. They also found negative effects in sperm count non-work-related causes, like long time use of the mobile phone [ 117 ].…”
Section: Lifestylementioning
confidence: 99%
“…One of the major reasons for this controversy may be that shift work consists of different work schedules, e.g., permanent night work and rotating shift work, which may lead to different health effects. A study of 1346 men in the community showed that rotating shift workers, but not permanent night workers, had lower sperm count compared to day workers ( Liu K. et al, 2020 ). In the same publication, social jetlag between work days and free days was found to be quantitatively associated with decreased sperm count in 796 male university students.…”
Section: Circadian Pathophysiology In Complex Diseasesmentioning
confidence: 99%
“…Moreover, when pregnant rats were exposed to constant light, their male offspring showed a decrease in numerous indicators, including testosterone levels, number of Sertoli cells, sperm count and normal sperm count ( Ogo et al, 2020 ). To simulate exposure to rotating shift work, a recent study put male mice into rotating light/dark cycles ( Liu K. et al, 2020 ). The authors found that the sperm count of the male mice decreased, while the circadian oscillation of sperm count was not affected.…”
Section: Circadian Pathophysiology In Complex Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, the clinical implications of shiftwork on reproductive dysfunction have been examined. Most of this work has focused on the female reproductive system, although some reports also show an impact on male reproductive status [ 2 , 3 ]; however, this literature is less explored. While several studies have provided strong correlational relationships between female shift workers and reproductive deficits throughout the reproductive cycle, including menstrual/ovulatory cycling [ 4 , 5 , 6 , 7 , 8 , 9 ], fertility and pregnancy [ 10 , 11 , 12 , 13 ], as well as labor and birth [ 14 , 15 , 16 , 17 , 18 ], there are still significant gaps in our knowledge of the mechanisms by which shiftwork may cause reduced reproductive function.…”
Section: Introductionmentioning
confidence: 99%